The End of Suffering: Mysticism, Messianism, and Medicine in Lubavitch - Dein, Simon (The journal of religion & society, 2019)
This paper examines understandings of evil, suffering, and sickness among Lubavitcher Hasidim, a group well known for their messianic assertions. It problematizes the relationship between theological teachings and how people use these ideas "on the ground" during periods of sickness. My focus is upon how these understandings are informed by their mystical text -Tanya - the Rebbe’s discourses, and through websites such as Chabad.org. On the one hand, Lubavitchers teach that evil is illusory, on the other, suffering will cease in the Messianic era. Furthermore, suffering is integral to the structure of the universe, human suffering will end following the cosmic repair. But how do these understandings impact their experience of sickness? For the most part, theology did not directly inform praxis and everyday cognition. Lubavitchers were concerned about practical alleviation of suffering.